A Shared Future : A Closer Look at Our Official Language Minority Communities - Canada. Office of the Commissioner of Official Languages (2024)
The Government of Canada’s key commitments as set out in Part VII of the Act are the basis of this report on the status of OLMCs. Although the vitality of OLMCs and the promotion of English and French continue to be paramount, the Act now also refers to the economic benefits of bilingualism and the importance of giving everyone in Canada the opportunity to learn a second official language. This report also includes an examination of the problems being experienced by the English-speaking communities of Quebec, whether in terms of the recognition of their rights, their perceived legitimacy as OLMCs, or their growing socio-economic vulnerability. As recent events have shown, the unique position of Quebec’s English-speaking communities within Canada’s linguistic landscape comes with its own set of challenges.
Keywords: Official Language Minority Community (OLMC)

Un avenir en commun : Regard sur nos communautés de language officielle en situation minoritaire - Canada. Office of the Commissioner of Official Languages (2024)
Les principaux engagements du gouvernement du Canada tels qu’énoncés dans la partie VII de la Loi sous-tendent cet état des lieux. L’épanouissement des CLOSM et la promotion du français et de l’anglais demeurent omniprésents, la Loi évoquant aussi désormais les bienfaits économiques du bilinguisme ainsi que l’importance de donner à toute personne au Canada la possibilité d’apprendre une deuxième langue officielle. Je me penche en particulier sur les problèmes auxquels sont confrontées les communautés d’expression anglaise du Québec, que ce soit sur le plan de la reconnaissance de leurs droits, de leur légitimité sur le plan des perceptions en tant que CLOSM ou de leur vulnérabilité socioéconomique croissante. Comme l’ont démontré de récents événements, la position unique des communautés de langue anglaise du Québec dans le paysage linguistique canadien s’accompagne de son propre lot de défis.
Keywords: Official Language Minority Community (OLMC)

Bâtir des ponts : Perceptions et réalités à propos des communautés d'expression anglaise du Québec et leur relation avec le francais au Québec et le bilinguisme au Canada - Canada. Office of the Commissioner of Official Languages (2024)
Le Commissariat aux langues officielles (le Commissariat) a observé qu’au cours des dernières années, les communautés d’expression anglaise du Québec (CEAQ) se sont souvent retrouvées au coeur du discours et des débats publics dans la province. Des données tirées de sondages et du recensement révèlent qu’en général, les communautés anglophones de la province sont en grande partie bilingues et qu’elles valorisent la dualité linguistique du Canada, y compris la langue française. L’on ignore, toutefois, dans quelle mesure la population générale est consciente de ces faits à propos des CEAQ et le Commissariat souhaitait vérifier l’hypothèse selon laquelle des mythes problématiques persistent. Dans ce contexte, et compte tenu de la modernisation de la Loi sur les langues officielles par le gouvernement fédéral en 2023, qui reconnaît la nécessité de « favoriser l’existence d’un foyer francophone majoritaire dans un Québec où l’avenir du français est assuré », ce projet de recherche est l’occasion de faire la lumière sur la relation que les communautés d’expression anglaise du Québec entretiennent avec la langue française dans la province et le bilinguisme officiel au Canada dans son ensemble. Ce projet permet aussi d’explorer la possibilité que les membres de la minorité anglophone du Québec soient considérés comme des bâtisseurs de ponts, ou même comme des alliés de la promotion du français au Canada, en vue de développer un discours plus constructif qui illustre clairement leurs contributions et, au bout du compte, vient déconstruire certaines perceptions erronées.
Keywords: Official Language Minority Community (OLMC)

Building Bridges : Perceptions and Realities About the English-speaking Communities of Quebec and their Relationship with French in Quebec and Bilingualism in Canada - Canada. Office of the Commissioner of Official Languages (2024)
The Office of the Commissioner of Official Languages (the Office of the Commissioner) has observed that, in recent years, the English-speaking communities of Quebec (ESCQ) have been the focus of much public discourse and debate in the province. Survey and census data indicate that, overall, the ESCQ are highly bilingual and value Canada’s broader linguistic duality, including the French language. The extent to which the general population is aware of these facets of the ESCQ is not clear, however, and the Office of the Commissioner wished to test the hypothesis that problematic myths may persist. In light of this context and with the modernization of the Official Languages Act by the federal government in 2023, which recognizes the need to “advance the existence of a majority-French society in a Quebec where the future of French is assured,” this research project is an opportunity to shed light on the relationship that the ESCQ have with the French language in Quebec and official bilingualism in Canada as a whole. This is also an opportunity to explore how Quebec’s English-speaking minority can be considered as bridge-builders or even as a potential ally of the promotion of French in Canada as a whole, with a view to developing a more constructive discourse that better acknowledges their contributions and, ultimately, deconstructs certain misperceptions.
Keywords: Official Language Minority Community (OLMC)

An Uphill Battle : Homelessness in Canada and Quebec and Its Likely Impact on the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Un défi de taille : Le sans-abrisme au Canada et au Québec et son impact potentiel sur la communauté québécoise d’expression anglaise - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2023-2024 - Canada. Office of the Commissioner of Official Languages (2024)

Better Understanding the Obligation to Take Positive Measures - Canada. Office of the Commissioner of Official Languages (2024)

Cultivate a Shared Future : A Closer Look at Our Official Language Minority Communities - Canada. Office of the Commissioner of Official Languages (2024)
Keywords: Official Language Minority Community (OLMC)

Cultivons un avenir en commun : Regard sur nos communautés de language officielle en situation minoritaire - Canada. Office of the Commissioner of Official Languages (2024)

Feuille de route sur les obligations des institutions fédérales en vertu de la partie VII de la Loi sur les langues officielles - Canada. Office of the Commissioner of Official Languages (2024)
La présente feuille de route est un guide pour aider les institutions fédérales et les membres du public à mieux comprendre la partie VII de la Loi sur les langues officielles (la Loi). Elle explique les objectifs de la partie VII ainsi que les engagements qui y sont affirmés, y compris les obligations corolaires applicables à toute institution fédérale assujettie à la Loi. Cette feuille de route se veut donc, avant tout, un outil pratique pour aider les institutions fédérales à saisir le sens de la partie VII de la Loi afin de pleinement la mettre en oeuvre. Il s’agit aussi d’un outil qui permettra aux communautés et aux particuliers visés par la partie VII de la Loi de mieux comprendre les droits que leur confère celle-ci. Enfin, cette feuille de route sert de complément d’information à la Loi elle-même, telle qu’elle est interprétée par le Commissariat aux langues officielles.

Making Progress Toward Substantive Equality : Principles to Guide the Development of Regulations for the Implementation of Part VII of the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2024)

Mieux comprendre l'obligation de prendre des mesures positives - Canada. Office of the Commissioner of Official Languages (2024)

Progresser vers l'égalité réelle : Principes visant à guider l'élaboration d'un règlement pour la mise en oeuvre de la Partie VII de la Loi sur les langues officielles - Canada. Office of the Commissioner of Official Languages (2024)

Rapport annuel : 2023-2024 - Canada. Office of the Commissioner of Official Languages (2024)

Roadmap for Federal Insitutions' Obligations Under Part VII of the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2024)
This roadmap was created to help federal institutions and the general public better understand Part VII of the Official Languages Act (the Act). It provides an explanation of the objectives of Part VII and the commitments set out in it, including the consequent obligations applicable to all federal institutions that are subject to the Act. The roadmap is first and foremost a practical tool to help federal institutions understand the meaning of Part VII of the Act so that they can fully implement it. It is also a tool to help communities and individuals covered by Part VII of the Act to better understand their rights under it. In addition, it serves as a complement to the Act itself, as interpreted by the Office of the Commissioner of Official Languages.

Mise à jour au sujet des frais de scolarité : Le gouvernement choisit une voie susceptible de ruiner les universités anglophones du Québec - Quebec Community Groups Network (QCGN) (2023)

Senate Standing Committee on Social Affairs, Science and Technology : Study on Bill C-35, An Act respecting early learning and child care in Canada - Quebec Community Groups Network (QCGN) (2023)

Senate Standing Committee on Official Languages (OLLO) : Study of C-13 An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2023)
The QCGN has participated in every step of the modernization of the Official Languages Act, beginning with Bill S-209; an initiative of this Chamber led by the Honourable Maria Chaput. English-speaking Quebec worked closely and in good faith with our Francophone counterparts in the rest of Canada, Ministers of Canadian Heritage and Official Languages and this Committee during its historic study to modernize the Act, beginning in 2017.

Définir les règlements de la partie vii de la Loi sur les langues officielles : Enjeux pour le Québec d’expression anglaise lors du processus - Quebec Community Groups Network (QCGN) (2023)

Producing Regulations for Part VII of the Official Languages Act : English-speaking Quebec’s Stake in the Process - Quebec Community Groups Network (QCGN) (2023)

Le QCGN prie instamment les parlementaires de garantir un avenir où le Québec d'expression anglaise est reconnu comme partenaire égal dans la nouvelle loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2022)

QCGN Urges Parliamentarians to Guarantee Future of English-speaking Quebec as Equal Partner in New Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Brief to the House of Commons Standing Committee on Official Languages on the Topic of Bill C-13, an Act To Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses and to Make Related Amendments to Other Acts - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
The present brief focuses on the first purpose, Bill C-13 amendments to the OLA. This is the topic on which I in my role as research associate at the Quebec English-Speaking Communities Research Network (QUESCREN) have developed the most knowledge.

Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes au sujet du projet de loi C-13 : Loi modifiant la Loi sur les langues officielles, édictant la Loi sur l’usage du français au sein des entreprises privées de compétence fédérale et apportant des modifications connexes à d’autres lois - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Le présent mémoire est axé sur le premier objectif — les modifications apportées à la LLO par le projet de loi C-13 —, car il s’agit du sujet sur lequel j’ai développé le plus de connaissances à titre d’attachée de recherche pour le Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN)

Modernizing the Official Languages Act : How the Federal Government Got it Wrong with C-13 - Quebec Community Groups Network (QCGN) (2022)

Legislative Brief to House of Commons and Senate Standing Committee(s) on Official Languages : Bill C-13, An Act to amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to other Acts (short title: An Act for the Substantive Equality of Canada’s Official Languages) - Task Force on Linguistic Policy (2022)
The TFLP submits that Bill C-13, the proposed modernization of the Official Languages Act (“OLA”), redefines and restructures Canada’s federal Official Languages framework in fundamental and, likely, undesirable ways. It introduces an unprecedented asymmetrical approach to the protection and promotion of Official Languages in Canada and, perhaps even more problematically, to the defence of the linguistic rights and recourses afforded to French speakers and English speakers, both in the Province of Québec, and across the country.

Use of French in Federally Regulated Private Businesses Act Abandons English-speaking Quebecers, QCGN Tells Senate Committee - Quebec Community Groups Network (QCGN) (2022)

Le QCGN propose des modifications majeures au projet de loi fédéral visant à moderniser la Loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2022)

QCGN Proposes Major Amendments to Federal Bill Modernizing the Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Brief to House of Commons Standing Committee on Official Languages : Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2022)
The Official Languages Act is a lifeline for English-speaking Quebec. With Quebec’s Bill 96, the community needs this lifeline more than ever. But with Bill C-13, this lifeline is fraying. Founded in 1995, the Quebec Community Groups Network (“QCGN”) is a not-for-profit organization linking English-language community organizations across Quebec. The QCGN—like the community it serves—is proud to support the protection and promotion of the French language in Canada. The QCGN advocates for linguistic duality in every province and territory. The English-speaking minority in Quebec is a diverse, bilingual, and resilient community that is facing serious economic challenges—in the face of persistent myths and stereotypes. Although the English language itself is not threatened, the English-speaking community’s challenge is in maintaining the community’s vitality and survival in all regions of Quebec.
Keywords: Official Language Minority Community (OLMC)

Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes : Projet de loi C-13, Loi visant l’égalité réelle entre les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2022)
La Loi sur les langues officielles (LLO) représente une bouée de sauvetage pour le Québec d’expression anglaise et, compte tenu du projet de loi 96 du Québec, la communauté anglophone en a besoin plus que jamais. Mais avec le projet de loi C-13, cette bouée de sauvetage s'effiloche. Fondé en 1995, le Quebec Community Groups Network (QCGN) est un organisme à but non lucratif qui relie les organismes communautaires de langue anglaise partout au Québec. Le QCGN — tout comme les communautés qu'il sert — est fier de soutenir la protection et la promotion de la langue française au Canada. Le QCGN milite en faveur de la dualité linguistique dans chaque province et chaque territoire. La minorité d’expression anglaise du Québec est une communauté diversifiée, bilingue et résiliente, qui est confrontée à de sérieux défis économiques ainsi qu’à des mythes et à des stéréotypes persistants. Bien que sa langue elle-même ne soit pas menacée, le défi de la communauté d’expression anglaise consiste à préserver sa vitalité et sa survie dans toutes les régions du Québec.
Keywords: Official Language Minority Community (OLMC)

Le QCGN réagit à la Loi modifiant la Loi sur les langues officielles et édictant la Loi sur l'utilisation du français dans les entreprises privées sous réglementation fédérale - Quebec Community Groups Network (QCGN) (2022)

QCGN Reacts to An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Business Act - Quebec Community Groups Network (QCGN) (2022)

Townshippers' Association Reacts to Bill C-32 - Townshippers' Association (2021)

QCGN Statement on Government of Canada’s Proposed Changes to the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Supports Commissioner's Call for Symmetry in the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network analyse préliminaire du projet de loi C-13 : Loi visant l’égalité réelle entre les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2021)
Rappelons que le présent document offre un aperçu du projet de loi C-13. Il ne s'agit pas d'une analyse exhaustive du projet de loi. Elle soutient et s’oriente plutôt vers les domaines prioritaires du QCGN.

Quebec Community Groups Network Preliminary Analysis of Bill C-13 : An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
This document presents an overview of Bill C-13. This is not a comprehensive analysis of the Bill. Rather, it is informed and directed at priority areas of the QCGN.

Federally Regulated Businesses and the New Languages Landscape - Quebec Community Groups Network (QCGN) (2021)

Ce que la population canadienne pense du bilinguisme officiel et de la Loi sur les langues officilles - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Official Bilingualism and the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2021)

Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Huge Victory for Minority School Boards in Supreme Court B.C. School Board Case - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

QCGN Intervienes in B.C. School Board Case at Supreme Court of Canada - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Memorandum of Understanding Between Acadians in New Brunswick, English-speaking Quebecers and Franco-Ontarians - Société de l’Acadie du Nouveau-Brunswick (SANB); Quebec Community Groups Network (QCGN); Assemblée de la francophonie de l’Ontario (AFO) (2019)
Keywords: Official Language Minority Community (OLMC)

Modernisation de la Loi sur les langues officielles : Recommandations du commissaire aux langues officielles pour une loi actuelle, dynamique et robuste - Canada. Office of the Commissioner of Official Languages (2019)
Cinquante années se sont maintenant écoulées depuis l’adoption de la toute première Loi sur les langues officielles. Alors que nous célébrons les succès et les avancées depuis 1969, le moment est propice de mener une réflexion approfondie sur les besoins des Canadiens en matière de langues officielles et de s’interroger sur la justesse des outils qu’offre la Loi pour y répondre adéquatement. En plus des nombreux appels lancés par le commissaire pour une modernisation de la Loi, de multiples demandes ont été formulées d’un bout à l’autre du pays par les deux groupes linguistiques. Ces demandes témoignent du besoin pressant de réviser le cadre législatif existant ainsi que d’élaborer de nouveaux règlements, et ce, afin de répondre aux attentes et à la réalité de chacun. C’est pourquoi le commissaire propose une modernisation de la Loi fondée sur une vision holistique. En effet, la vision qu’il recommande va bien au-delà de modifications de nature législative et réglementaire. Il s’attend à ce que les modifications qui seront adoptées mènent à un changement de culture afin que la dualité linguistique puisse pleinement s’épanouir partout au Canada. Pour y arriver, le commissaire propose 18 recommandations, chapeautées par les trois piliers sur lesquels repose sa vision : une loi actuelle, dynamique et robuste.

Modernizing the Official Languages Act : The Commissioner of Official Languages' Recommendations for an Act that is Relevant, Dynamic and Strong - Canada. Office of the Commissioner of Official Languages (2019)
It has been 50 years since the first Official Languages Act was passed. While we celebrate the progress and many successes achieved since 1969, it is a good time to conduct and in-depth review of official languages needs and think about whether the tools offered by the Act meet those needs effectively. The Commissioner’s repeated calls to modernize the Act have been echoed across Canada by both language groups, highlighting the urgent need to review the current legislative framework and draft new regulations to meet the expectations and reflect the realities of all Canadians. The Commissioner is therefore recommending a holistic approach to modernizing the Act that goes well beyond legislative and regulatory change. To create a cultural shift so that linguistic duality can reach its full potential across Canada, he has made 18 recommendations under the three pillars of his vision for an Act that is relevant, dynamic, and strong.

[Letter to René Cormier, Chair of the Senate Standing Committee on Official Languages, from Geoffrey Chambers, QCGN President, re: the Official Languages Act] - Chambers, Geoffrey (2018)

Brief by the Consortium of Official Language Minority Community Media, Presented to the Standing Senate Committee on Official Languages Within the Context of its Study on Canadians' Views About Modernizing the Official Languages Act - Sonier, Francis; Demers, Paul; Bonspiel, Steve (2018)
The Consortium of Official Language Minority Community Media (the Consortium) is an alliance of the three national organizations representing official language minority community media in Canada: the Association de la presse francophone (APF), the Alliance des radios communautaires du Canada (ARC du Canada) and the Quebec Community Newspapers Association (QCNA). Since 2016, the Consortium has been the common voice of all three of its members on a number of issues.
Keywords: Official Language Minority Community (OLMC)

QCGN Applauds Priorities in Commissioner's Annual Report - Quebec Community Groups Network (QCGN) (2018)

QCGN Advocates for More Flexible Regulations for Provision of Federal Minority Language Services - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN Approves New Roadmap for Canada's Official Languages - Quebec Community Groups Network (QCGN) (2013)

Roadmap to Canada's Linguistic Duality 2008-2013 - Donnelly, Robert (2010)
Remarks to the Standing Committee on Official Language
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Learning from the Past - Donnelly, Robert (2010)
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Looking to the Future - Johnston, Nicola (2010)
Remarks to the Standing Committee on Official Languages

What is Bill C-32? - English Language Arts Network (ELAN) (2010)
Bill C-32 is officially known as the Copyright Modernization Act. It was an attempt at a “Balanced Copyright” act introduced in Parliament on June 2, 2010, by the Conservative Party — Honourable Tony Clement, Minister of Industry, and the Honourable James Moore, Minister of Canadian Heritage and Official Languages. It contains changes to Canadian Copyright Law that are hotly contested by artists and authors of cultural media. The Bloc, NDP and Liberal parties are opposed to the act being passed in its current state, and are calling for amendments to be made.
Keywords: Official Language Minority Community (OLMC)